Taxi Drivers’ Cross-Cultural Communication Problems and Challenges in Bangkok, Thailand - Thadphoothon, Janpha (Journal of Reviews on Global Economics, 2017)
This paper reports an investigation of Thai taxi drivers’ cross-cultural communication problems and challenges by synthesizing the research findings from two related studies: (1) a classroom investigation of Thai taxi drivers’ communication challenges; and (2) a study of Thai taxi drivers’ English language competence. The findings reveal that Thai taxi drivers had relatively low level of English competence, and had experienced three cross-cultural communication problems and challenges in the language, cultural, and attitudinal domains. Efforts to improve their English skills need to take into consideration the nature of their work and work conditions.